СТАН І ПЕРСПЕКТИВИ УДОСКОНАЛЕННЯ НАВЧАННЯ ХІМІЇ СТУДЕНТІВ ФАРМАЦЕВТИЧНОГО ФАКУЛЬТЕТУ НАЦІОНАЛЬНОГО МЕДИЧНОГО УНІВЕРСИТЕТУ ІМЕНІ О. О. БОГОМОЛЬЦЯ - Рева, Тетяна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто сучасний стан хімічної підготовки майбутніх провізорів. Визначено основні чинники, що негативно впливають на якість хімічної освіти в системі фармацевтичної освіти. Запропоновано напрями модернізації змісту навчання. Аналіз результатів підтвердив доцільність змін у змісті навчання та необхідність спеціально організованого процесу викладання хімічних дисциплін на основі інтегрованого підходу, ефективність якого може забезпечити певна побудова курсів, певні форми і методи навчання. В статье рассмотрено современное состояние подготовки провизоров по химии. Определены основные факторы, которые негативно влияют на качество химического обучения в системе фармацевтического образования. Предложены направления модернизации содержания обучения. Анализ результатов подтвердил целесообразность изменений в содержании обучения и необходимость специально организованного процесса преподавания химических дисциплин на основе интегрированного подхода, эффективность которого может обеспечить определенное построение курсов, определенные формы и методы обучения. The modern state of chemical training of future pharmacists is reviewed in the article. Basic factors that negatively influence on the quality of chemical education in the system of pharmaceutical education are considered. Directions of modernisation of study maintenance are offered. The importance of the study of chemical disciplines consists in the fact of being theoretical basis for learning technological disciplines (pharmaceutical technology of drugs, industrial technology of drugs, pharmaceutical technology of cosmetic products, etc.), cycle of practical training and mastering of the chosen profession in general. Analysis of the results confirmed the feasibility of changes in the context of education and the need of specially organized process of teaching of chemical disciplines based on an integrated approach. It can ensure the effectiveness of certain construction courses, certain forms and methods of teaching.